The Incidence and Prevalence of Systemic Lupus Erythematosus in San Francisco County, California: The California Lupus Surveillance Project. Issue 10 (10th September 2017) - Dall'Era, Maria; Cisternas, Miriam G.; Snipes, Kurt; Herrinton, Lisa J.; Gordon, Caroline; Helmick, Charles G.
Abstract : Objective: Estimates of the incidence and prevalence of systemic lupus erythematosus (SLE) in the US have varied widely. The purpose of this study was to conduct the California Lupus Surveillance Project (CLSP) to determine credible estimates of SLE incidence and prevalence, with a special focus on Hispanics and Asians. Methods: The CLSP, which is funded by the Centers for Disease Control and Prevention, is a population‐based registry of individuals with SLE residing in San Francisco County, CA, from January 1, 2007 through December 31, 2009. Data sources included hospitals, rheumatologists, nephrologists, commercial laboratories, and a state hospital discharge database. We abstracted medical records to ascertain SLE cases, which we defined as patients who met ≥4 of the 11 American College of Rheumatology classification criteria for SLE. We estimated crude and age‐standardized incidence and prevalence, which were stratified by sex and race/ethnicity. Results: The overall age‐standardized annual incidence rate was 4.6 per 100, 000 person‐years. The average annual period prevalence was 84.8 per 100, 000 persons. The age‐standardized incidence rate in women and men was 8.6 and 0.7 per 100, 000 person‐years, respectively. This rate was highest among black women (30.5), followed by Hispanic women (8.9), Asian women (7.2), and white women (5.3). The age‐standardized prevalence in women per 100, 000 persons was 458.1 in blacks, 177.9 in Hispanics, 149.7 in Asians, and 109.8 in whites. Capture–recapture modeling estimated 33 additional incident cases and 147 additional prevalent cases. Conclusion: Comprehensive methods that include intensive case‐finding provide more credible estimates of SLE in Hispanics and Asians, and confirm racial and ethnic disparities in SLE. The disease burden of SLE is highest in black women, followed by Hispanic women, Asian women, and white women.